Prevalence and Antibiotic Susceptibility Profile of Escherichia coli and Klebsiella spp. Isolates from Urine Samples of Suspected Urinary Tract Infection Patients Attending Nisa Premier Hospital, Abuja, Nigeria - Nasiru Abdullahi; Uju Mirian Oranekwulu (Nigerian Journal of Medicine)
Background: Urinary tract infections (UTIs) account for one of the major reasons for most hospital visits, and Escherichia coli and Klebsiella spp. have been reported to be the most commonly encountered aetiologic agents. Knowledge of the antibiotic susceptibility patterns of these organisms in a particular geographical area is, therefore, essential for choosing an appropriate empirical antimicrobial treatment. Aim: The aim of this study was to determine the prevalence and antibiotic susceptibility patterns of E. coli and Klebsiella spp. isolates from urine samples of suspected UTI patients attending Nisa Premier Hospital, Abuja. Methods: This study was a retrospective analysis of the data on E. coli and Klebsiella spp. isolated from urine samples using standard microbiological methods at the Medical Microbiology Unit of the Department of Laboratory Services of Nisa Premier Hospital, Abuja, over a period of four months (13th June, 2022–13th October, 2022). Results: E. coli was the most commonly encountered bacterial isolates accounting for 29.8% of all the uropathogens, followed by Klebsiella spp. 27.0%. Both E. coli and Klebsiella spp. exhibited very high (100%) susceptibility to imipenem and meropenem (89.0% vs. 81.1%). They were respectively poorly susceptible to ciprofloxacin (26.9% vs. 25.6%), nitrofurantoin (46.2% vs. 11.1%), cefuroxime (10.5% vs. 36.8%), gentamicin (41.3% vs. 46.9%) and piperacillin–tazobactam (16.0% vs. 12.2%). Conclusion: E. coli and Klebsiella spp. were the most commonly encountered uropathogens. Imipenem and meropenem are excellent choices for empiric treatment of UTI due to these pathogens in this environment.